Conformal noble metal high-entropy alloy nanofilms by atomic layer deposition for an enhanced hydrogen evolution reaction - Jing, Lin (2023)
The current synthesis methods of high-entropy alloy (HEA) thin-film coatings face huge challenges in facile preparation, precise thickness control, conformal integration, and affordability. These challenges are more specific and noteworthy for noble metal-based HEA thin films where the conventional sputtering methods encounter thickness control and high-cost issues (high-purity noble metal targets required). Herein, for the first time, we report a facile and controllable synthesis process of quinary HEA coatings consisting of noble metals (Rh, Ru, Pt, Pd, and Ir), by sequential atomic layer deposition (ALD) coupled with electrical Joule heating for post-alloying. Furthermore, the resulting quinary HEA thin film with a thickness of ∼50 nm and an atomic ratio of 20:15:21:18:27 shows promising potential as a platform for catalysis, exhibiting enhanced electrocatalytic hydrogen evolution reaction (HER) performances with lower overpotentials (e.g., from 85 to 58 mV in 0.5 M H2SO4) and higher stability (by retaining more than 92% of the initial current after 20 h with a current density of 10 mA/cm2 in 0.5 M H2SO4) than other noble metal-based structure counterparts in this work. The enhanced material properties and device performances are attributed to the efficient electron transfer of HEA with the increased number of active sites. This work not only presents RhRuPtPdIr HEA thin films as promising HER catalysts but also sheds light on controllable fabrication of conformal HEA-coated complex structures toward a broad range of applications.